Clinical Validation of a Miniature Nuclear Probe System for Continuous On-line Monitoring of Cardiac Function and ST-Segment - Broadhurst, Paul; Cashman, Peter; Crawley, John; Raftery, Edward; Lahiri, Avijit (The Journal of nuclear medicine (1978), 1991)
A new, miniature cesium iodide/photodiode nuclear probe (the "Cardioscint") has been developed for continuous on-line measurement of left ventricular function and the ST-segment. Ejection fraction (EF) measurements in 77 patients were compared with gated equilibrium radionuclide ventriculograms. The probe was positioned over the left ventricle by first using a blind positioning algorithm and then by using the gamma camera. Background was measured both manually and automatically. There was good correlation between probe (positioned blind) and gamma camera EF with both manual (r = 0.80, n = 65) and automatic (r = 0.78, n = 66) backgrounds. Use of the gamma camera did not significantly alter the results. Correlation between the probe stroke counts and thermodilution-derived stroke index during atrial pacing in six subjects was also satisfactory (r = 0.69, n = 102). Thus, the Cardioscint is able to provide a reliable estimate of EF and can track rapid changes in cardiac volumes.